The role of peroxisome proliferator activated receptor alpha (PPARα) in the effect of piroxicam on colon cancer - McCartney, Karen M. (2015)
Studies with APCMin/+ mice and APCMin/+ PPARα-/- mice were undertaken to investigate whether polyp development in the mouse gut was mediated by PPARα. Additionally, the effect of piroxicam treatment dependency on PPARα was assessed.